The Bidens : inside the first family's fifty-year rise to power - Schreckinger, Ben (New York : Twelve, 2021)
An exploration of Joe Biden as told through his extended family.
In November 2020, Americans did not just elect Joe Biden: they got a package deal. The entire Biden family are sure to play a defining role in his presidency, just as they have in every one of his endeavors. Schreckinger believes the best way to understand Biden-- his values, fears and motives-- is to understand his family. He explores their Irish (and not-so-Irish) roots, their dodgy business deals, and their personal struggles and triumphs alike. -- Adapted from jacket
Chekhov's laptop -- The clan -- The children's crusade -- How the Bidens became Irish -- Glory days -- Working men -- Trial run -- Domestic policy -- Dynastic Delaware -- The Delaware way -- The Bidens go global -- Vice Presidential perks -- Frank -- Dynasty deferred -- The notorious R.H.B. -- The plot against the Bidens -- The "laptop from hell."
Includes bibliographical references (pages 253-293) and index.
109127
Keywords: Biden, Joseph R., -- Jr; Biden, Joseph R., -- Jr. -- Family; Presidents -- United States -- Biography; Presidents -- United States -- Family -- Biography; Politicians -- United States -- Biography; United States -- Politics and government -- 2017-2021.; Biographies